ANALYZING THE IMPLEMENTATION OF TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) BY EFL TEACHERS IN THE CLASSROOM - Nurdin, Nurhasanah; Anugrawati, Nunung; Mannong, Andi Bulkis Maghfirah (FKIP Unismuh Makassar, 2023)
This research aimed to find out the implementation of Technological Pedagogical Content Knowledge (TPACK) in EFL classroom at SMPN 4 Sungguminasa and the teachers perception on the implementation of Technological Pedagogical Content Knowledge (TPACK) in EFL classroom. The data was collected in September from two teachers of seventh and eighth grade of SMPN 4 SUNGGUMINASA. This research used a descriptive qualitative method, and the instruments used observation and interview. The observation was used to observe the implementation of TPACK in EFL classroom and the interview used to get the data related the teachers’ perception on the implementation of TPACK in EFL classroom.The result of this research showed that the teachers in SMPN 4 SUNNGUMINASA have a good level of TPACK they can operate technology variance and manage classes in teaching EFL classroom, namely learning tools and applications such LCD projectors, power point, Laptops, Google Classroom, WhatsApp, mantimeter.com and YouTube. They have done quite well in the teaching and learning process. The result of the interview of this research showed that mostly the teachers gave positive perception and agreed that teachers use Information Communication and Technology (ICT) in EFL classroom, students more motivated to study and easy to understand the material.